Penetrating words: a Babylonian Rabbinic response to Syriac Mariology - Rosenberg, Michael (The journal of Jewish studies, 2016)
Recent research has emphasized the extent of a shared cultural context for Rabbinic Judaism and early Christianity, especially in the Roman East and the western portions of the Sasanian Empire. This article argues that a challenging passage in Tractate Ketubot of the Babylonian Talmud is best explained in light of tropes about the Virgin Mary and the Annunciation that were particularly common and beloved in Syriac Christian texts. This finding not only supplements the growing body of evidence for cultural ties between these two communities, but also suggests that the character Mary and questions around virginity were particularly appealing and/or contested topics for the rabbis and/or their audience.